PEMBERIAN MASSAGE FRICTIONDAN ISCHEMIC COMPRESSION TECHNIQUE LEBIH EFEKTIF DIBANDINGKAN PEMBERIAN MYOFASCIAL RELEASE TECHNIQUE UNTUK MENURUNKAN NYERI TENSION HEADACHE PADA STAFF PENGAJAR DI SMKN 5 DENPASAR - I Gede Wisnu Pramadita; Ari Wibawa; Susy Purnawati (Majalah Ilmiah Fisioterapi Indonesia, 2017)
Abstract The combination of Massage Friction with Ischemic Compression Technique and Myofascial Release Technique is the intervention used and compared to reduce the pain of Tension Headache on the teaching staff at SMKN 5 Denpasar.This research is experimental research with Randomized Purposive Sampling design. The sample consists of 18 people divided into 2 groups. Treatment Group 1 was given Intervention Massage Friction and Ischemic Compression Technique and Treatment Group 2 was given Myofascial Release Technique Intervention. The mean difference of Tension Headache headache decrease in treatment group 1 was 1.00 and in treatment group 2 was 0.46 with (p <0,05). It was concluded that the Massage Friction and Ischemic Compression Technique Intervention was more effective than Myofascial Release Technique in reducing Tension Headache headache on the teaching staff at SMKN 5 Denpasar. Keywords : Tension Headache, Massage Friction, Ischemic Compression Technique, Myofascial Release Technique